Formulation of Sorghum-Based High-Protein Crackers Enriched with Wheat and Soybean Flours for Toddlers - Afan Bagus Mananda; Danu Indra Wardhana; Andika Putra Setiawan; Anisa Nurina Aulia; Fina Syafia (Agroindustrial Technology Journal, 2025)
Various complementary food menus have been developed to support parents in selecting nutritious first foods for toddlers. These foods are commonly based on rice flour as a carbohydrate source. However, the high reliance on rice has driven diversification efforts toward alternative staples. This study explores high-protein biscuits formulated from sorghum flour and soybean flour as potential complementary foods for stunted toddlers. Sorghum provides complex carbohydrates and fiber, while soybean flour contributes high-quality plant-based protein. Five different formulations (F0–F4) were tested using a Completely Randomized Design (CRD) with two replications per treatment, each involving three sample units. The chemical properties analyzed included moisture, ash, fat, protein, and carbohydrate content. One-way ANOVA followed by Duncan's multiple range test (α = 0.05) was applied to assess significant differences. The results showed statistically significant differences (p < 0.05) among the formulas in terms of protein and fat content. Protein content ranged from 5.21% to 7.66%, and fat ranged from 7.8% to 9.55%. F3 was selected as the best formulation due to its optimal balance of nutrients, highest protein content (7.66%), and compliance with Indonesian National Standard (SNI) for biscuits. Its full nutritional profile includes 3.7% moisture, 1.52% ash, 9.55% fat, 7.66% protein, and 77.7% carbohydrates. Given that toddlers aged 1–3 years require approximately 20 g/day of protein and 1,125 kcal/day, this product can contribute meaningfully to their daily intake. Thus, sorghum–soybean biscuits demonstrate potential as nutritious complementary foods to help address protein-energy malnutrition and reduce the prevalence of stunting in toddlers. Thus, biscuits made from sorghum and soybean flour can be an alternative nutritious food supplement for toddlers. It is recommended that these crackers be further fortified with other important nutrients such as iron, zinc, and vitamin A, which also play a role in preventing stunting.